Unusual Manifestations of a Rare Clinical Entity: Erdheim-Chester Disease - Martins,Nuno (2019)
A 69-year-old woman presented with sudden left hemiparesis. Computed tomography (CT) scan excluded acute brain injuries. Patient was admitted with acute ischemic stroke of right hemisphere. There was full recovery within 24 hours and etiologic studies were normal. There was a concomitant history of ingestion of 6 litres of water per day over the previous 2 years. Water deprivation test followed by the administration of desmopressin confirmed central diabetes insipidus diagnosis. Brain magnetic resonance imaging (MRI) was normal. Full body CT scan showed arterial wall thickening suggestive of large and medium vessels vasculitis, retroperitoneal fibrosis, perinephric infiltration, pleural and pericardial thickening and diffuse densification of greater omentum. Angio-MRI showed occlusive micro-arterial injuries. Laparoscopic biopsy of greater omentum revealed multinucleated giant Touton CD68+, CD1A- cells. This finding is pathognomonic of Erdheim-Chester Disease, a rare non-Langerhans histiocytosis.